2013
DOI: 10.1002/asia.201300858
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Ge@C Core–Shell Nanocomposites for High‐Performance Lithium Storage in Lithium‐Ion Batteries

Abstract: Herein, we report a facile and "green" synthetic route for the preparation of Ge@C core-shell nanocomposites by using a low-cost Ge precursor. Field-emission scanning electron microscopy and transmission electron microscopy analyses confirmed the core-shell nanoarchitecture of the Ge@C nanocomposites, with particle sizes ranging from 60 to 100 nm. Individual Ge nanocrystals were coated by a continuous carbon layer, which had an average thickness of 2 nm. When applied as an anode materials for lithium-ion batte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
2
29
0
1
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the electrolyte to form solid electrolyte interphase (SEI) film, resulting in the capacity loss during the first cycle. 21,57,58 The large peak between 0 and 0.51 V is assigned to the reduction of Ge. From the second cycle onward, three apparent peaks located at 0.01, 0.31, and 0.48 V can be attributed to the formation of Li x Ge alloy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the electrolyte to form solid electrolyte interphase (SEI) film, resulting in the capacity loss during the first cycle. 21,57,58 The large peak between 0 and 0.51 V is assigned to the reduction of Ge. From the second cycle onward, three apparent peaks located at 0.01, 0.31, and 0.48 V can be attributed to the formation of Li x Ge alloy.…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Nevertheless, the practical application of Ge is hindered by the pulverization problem caused by the large volume changes during Li insertion/extraction processes, thus leading to the loss of electrical conductivity and consequently a rapid capacity decline upon cycling. [26][27][28][29][30][31] Previously studies have demonstrated that decreasing the Ge particle size into the nanometer range could alleviate the stress produced during Li uptake and release processes and suppress the tendency of the nanostructure to fracture.…”
Section: Introductionmentioning
confidence: 99%
“…synthesized two Ge/C hybrids with clustered and non‐clustered nanostructures that were both located inside hollow carbon shells . In 2013, a facile solution‐phase‐reduction method was employed to synthesize Ge@C nanocomposites . The as‐prepared Ge@C hybrid, which was coated with a continuous carbon layer with an average thickness of 2 nm, maintained a reversible capacity of 907 mA h g −1 at 4 A g −1 .…”
Section: Germaniummentioning
confidence: 99%
“…reported a facile method to prepare Ge@C core–shell composites. The evaluated electrochemical performance indicated that the composites can deliver a high capacity up to 734 mA h g −1 at 0.8 A g −1 14. Guo et al.…”
Section: Introductionmentioning
confidence: 96%
“…With a theoretical specific capacity of 1600 mAh g −1 , four times higher than that of conventional graphite anode, germanium (Ge) is an excellent candidate as an anode material for LIBs 1014. It exhibits not only good lithium conductivity (400 times faster than Si), but also high electrical conductivity (104 times higher than Si).…”
Section: Introductionmentioning
confidence: 99%